Um estudo da construção aspectual [dormir particípio] no português brasileiro contemporâneo - Ana Paula Rabelo de Freitas (2022)
We have studied in a panchronic research the grammaticalization process of the verb to sleep (dormir) in constructions with the past participle to mark the aspectual category in contemporary Brazilian Portuguese from a functionalist perspective of language studies. For such we carried out an investigation into the grammaticalization process and its assumptions (cf. KURYŁOWICZ, 1975[1965]; HOPPER, 1991; TRAUGOTT & DASHER, 2004; HEINE et al, 1991; 2003; LEHMANN, 2015 [1982], among others) in order to test our main hypothesis that in constructions such as [The door has slept open] (A porta dormiu aberta) the verb presents itself as copulative to mark aspect, thus ceasing to be lexical. Considering the grammatical function assumed by the verb to sleep (dormir) we have proposed a discussion about the verbal category of aspect supported by classic studies (CASTILHO, 1968; 2020 & TRAVAGLIA, 2014[1981]). Thus, by considering the lexical-syntactic nature of the aspectual category, it was possible to verify a second hypothesis: the main aspect marked by the studied construction is the durative. Our linguistic sample was comprised of 2.386 (two thousand three hundred and eighty-six) points of data collected in the Portuguese Corpus (DAVIES; FERREIRA, 2006), and in the social network Twitter. They were then quantitatively analyzed according to the following criteria: syntactic (context of form predication) and semantic (form abstraction and subject animacy). Due to the hypothesis that we were facing an emergent phenomenon, we analyzed the data qualitatively according to the grammaticalization principles proposed by Hopper (1991). We have considered that cognitive, syntactic, and semantic factors were involved in the process of reanalysis of the verb which loses its predicative property that is displaced to the term on the right side of the verb, as proposed by Castilho (2020). Therefore, we have identified the contexts of restrictions for the reanalysis of the studied form: cognitively, from the corporal experience of the speaker, it was possible to verify that the grammaticalized form maintains traces of the etymologic sense of the lexical form in the process of semantic abstraction of the verb, which gradually loses its notional content while embodying the grammatical function. The predicative context (nominal predicate with past participle in the predicative function) has set up the syntactic restriction that was observed. The semantic restriction is noted in the requirement of the [- animacy] trace of the subject that constitutes the construction. The analysis undertaken allowed us to confirm our main hypothesis of grammaticalization, as well as to propose a cline of the categorial status of the verb to sleep (dormir) [significative form > relational form] in constructions with the past participle according to the predicative contexts: verbal predicate > verbal-nominal predicate > nominal predicate.